2021
DOI: 10.1016/j.eats.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic-Assisted Acromioclavicular Joint Dislocation Repair: A Modified Technique for Horizontal Stabilization Using Suture Anchors

Abstract: Acromioclavicular (AC) dislocation is a common lesion often resulting from a sports injury. Nowadays, treatment is still controversial mainly in grade III lesions according to the Rockwood classification. For most surgically treated AC acute dislocations, treatment is performed with an arthroscopic procedure that anatomically reconstructs the coracoclavicular ligaments. Increasing knowledge about AC joint biomechanics has underlined the importance of its horizontal stability through the superior and inferior A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Numerous surgical techniques have been described for the treatment of acute AC joint dislocation. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 The goals of the new anatomic CC ligament reconstruction techniques are to achieve anatomic reduction of the ACJ and adequate fixation in order to allow and facilitate primary healing of AC and CC ligaments, and also to minimize the risk of associated complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous surgical techniques have been described for the treatment of acute AC joint dislocation. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 The goals of the new anatomic CC ligament reconstruction techniques are to achieve anatomic reduction of the ACJ and adequate fixation in order to allow and facilitate primary healing of AC and CC ligaments, and also to minimize the risk of associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical and clinical studies have confirmed that good to excellent results are expected with these techniques. 9 , 10 , 11 , 12 , 13 , 14 , 15 A skillful arthroscopic surgeon can take advantage of recent advances in implant designs and perform arthroscopically assisted or fully endoscopically assisted procedures such the anatomic ACJ stabilization procedure. These arthroscopic techniques have the advantage of a minimally invasive approach, facilitate management of associated intraarticular lesions, and offer adequate visualization of the coracoid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The have improvised with arthroscopic assisted double row repair AC joint injuries trying to stabilisze the vertical and horizontal s t a b i l i t y a n d r e p l i c a t e t h e coracoclavicular ligament function. [20,21].…”
Section: Acromioclavicular Joint Repair /mentioning
confidence: 99%